Effects of the Stacking Sequence, Material Nature and Addition of an Adhesive Film on the Delamination Resistance of Woven Composite Laminates in Mode I and II. Issue 1 (January 2015) - Navarro, P.; Aubry, J.; Pascal, F.; Marguet, S.; Ferrero, J.F.; Dorival, O.
Woven composites are well-known for their good transverse properties and for their high fracture toughness. The damage mechanisms leading to delamination in woven composites are identified in mode I and II and are compared with those occurring in unidirectional laminates. The influence of several parameters, including the draping sequence and the fibre / matrix interface on the fracture toughness of woven composite laminates is studied. Pure Mode I and Mode II tests are carried out on several carbon/epoxy and glass/epoxy woven composites configurations and the differences observed are discussed from a fractographic point of view. The study illustrates the high fracture toughness of the composites made of woven fabrics as well the influence of the orientation of the plies, the nature of the fibres and the addition of an adhesive film.